At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Alright, so, we have 3(y+4) = 24
So, here is what we are going to do:
3(y+4) = 24
= 3*Y + 3*4 = 24
= 3Y + 12 = 24
Next up, we want to get rid of the 12.
= 3Y + 12 -12 = 24
= 3Y = 24
= 3Y/3 = 24/3
= Y = 8
So, here is what we are going to do:
3(y+4) = 24
= 3*Y + 3*4 = 24
= 3Y + 12 = 24
Next up, we want to get rid of the 12.
= 3Y + 12 -12 = 24
= 3Y = 24
= 3Y/3 = 24/3
= Y = 8
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.